Influence of an original manufacturing process on the properties and microstructure of SiC/SiC tubular composites. (August 2019) - Braun, James; Sauder, Cédric; Lamon, Jacques; Balbaud-Célérier, Fanny
Abstract: SiC/SiC composites reinforced with Hi-Nicalon S 3rd generation SiC fibers are promising candidates for high temperature aeronautical applications and fuel cladding in nuclear reactors. An original patented process was used to produce SiC/SiC tubular samples for dimensional and tensile mechanical characterizations. The process route is described in detail to further understanding of specific features. SiC/SiC samples show a low porosity and excellent geometrical tolerance. Highly reproducible tensile mechanical behavior is observed with good mechanical failure characteristics. Some specific features were highlighted during mechanical characterizations with loading/unloading sequences. For instance, an original mechanical behavior was observed before the onset of matrix multicracking (deviation from linearity). To our knowledge, it is the first time that this kind of behavior has been detected on SiC/SiC composites, due to the processing route leading to the microstructure of specific samples.